(untitled) (Rajarshi Janak University Research Journal, 2024)
A vast number of biomass-based materials are getting increasing attention for heavy metal removal and recovery due to their good performance, low cost, large availability, and environmental friendliness. This study primarily aims to fabricate a cost-effective, potent adsorbent derived from walnut shells through chemical modification, targeting the removal of Pb(II) ions from water. The experimentation involves the preparation of adsorbents from charred walnut shell (CWS) and xanthated walnut shell (XWS), followed by batch trials to eradicate Pb(II) from water. Parameters for instance pH, concentration of Pb(II), adsorbent quantity, and contact duration were examined using both CWS and XWS adsorbents. For characterization purposes, FTIR, XRD, and FE-SEM analyses were employed. Optimal conditions were identified at pH 4 and duration of contact 150 minutes for both adsorbents. Equilibrium sorption data adhered best to the Langmuir isotherm model, with maximum adsorption capacities of 61 mg/g for CWS and 109.9 mg/g for XWS. Kinetic modeling showed the well-fitting of pseudo-second order kinetic. These findings suggest that XWS presents a promising, eco-friendly alternative bioadsorbent intended for the elimination of lead (II) from water.